Performance Evaluation Practices of Select Higher Education Institution in the City of Manila: Basis for Enhancing Faculty Performance - Gutierrez, Ernell Bautista (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Performance evaluation practices for faculty members has been an effective method to improve faculty performance, thus, educational institution must give paramount importance on ways to improve the performance of their faculty members. Indicated in the study of Mamatha, H et al (2021), higher education institutions being the major economic drivers in a nation rely on their faculty for quality of education. Traditional methods of performance evaluation based on quantitative data are more of a mathematical calculation than a scientific approach. The research sought answers to the effectiveness of evaluation practices in terms of student evaluation, peer evaluation and immediate superior evaluation as mechanism to enhance performance of faculty members. The research employed a quantitative-descriptive methodology and the main participants in the research are academic heads and faculty members. Results revealed that, the current evaluation practices of the select educational institution are effective as assessed by the participants. In terms of identifying differences, results revealed that between academic head and faculty members, there was no significant difference in the assessment about student evaluation, peer evaluation and immediate superior evaluation. On the other hand, when faculty members are categorized in terms of employment status, result revealed that their assessment differs on the three evaluation practices.